Impact of news-based equity market volatility on international stock markets - Abdullah Alqahtani; Michael J. Wither; Zhankui Dong; Kimberly R. Goodwin (Journal of Applied Economics, 2020)
This study examines the long run impacts of equity market volatility on index returns of nine major international stock exchanges in the Western and Asian regions. This study employs the text-based Economic Market Volatility (EMV) index to measure the degree of uncertainty in the U.S. stock market. Using monthly data from December 2001 to August 2018, the estimation results derived using the standard and nonlinear ARDL models deliver several key messages. First, rising U.S. stock market volatility exhibits significant and negative impacts on stock market returns, except for the stock markets of China, Hong Kong, and India whose impacts are negative but insignificant. Second, the use of the nonlinear ARDL model does not show any signs of asymmetry in the relationship between stock market returns and changes in the EMV index, suggesting that the change in the EMV index has symmetric effects on the changes in major stock indices.
Keywords: 330; Equity market volatility index; international investment; vector autoregressive